Aboutness and Conceptual Analysis: A Review. Issue 2 (13th April 2021) - Holley, Ralph M.; Joudrey, Daniel N.
Abstract: The purpose of this paper is to provide an overview of aboutness and conceptual analysis, essential concepts for LIS practitioners to understand. Aboutness refers to the subject matter and genre/form properties of a resource. It is identified during conceptual analysis, which yields an aboutness statement, a summary of a resource's aboutness. While few scholars have discussed the aboutness determination process in detail, the methods described by Patrick Wilson, D.W. Langridge, Arlene G. Taylor, and Daniel N. Joudrey provide exemplary frameworks for determining aboutness and are presented here. Discussions of how to construct an aboutness statement and the challenges associated with aboutness determination follow.